Revitalization of Funding for Savings and Loans Cooperatives As Efforts To Improve The State’s Economy After The Covid-19 Pandemic - Hassanain Haykal; Theo Negoro; Livany Adeline (Yustisia, 2021)
This research aims to analyze the government's possible strategies to empowering cooperatives as an alternative means of channeling financing after the Covid-19 Pandemic in Indonesia. Basically, cooperatives are business media for enhancing the standard of living in a family, and are referred to as the pillars of the national economy. The study was also carried out in order to provide a regulatory solution regarding the revitalization of cooperatives, in strengthening the organisation, especially in the financial aspect. The normative juridical approach, was used, also known as the doctrinal legal technique. The results showed that the cooperatives required significant organizational changes, such as strengthening the implementation of good governance regulations, conducting financial agreements, as well as managing income and human resources. Furthermore, significant organizational changes were achieved by forming a ministerial regulation, to regulate good governance, enact internal rules, create a code of conduct, and establish a financial system with legal agreement among the cooperative members.